Visiting with Elders—Aging, Caregiving, and Planning for Future Generations of American Indians and Alaska Natives - Cole Allick; Marija Bogic (Genealogy)
(1) Background: To address the importance of engaging American Indian and Alaska Native Elders in a dialogue about healthy aging and fill the gap in the scholarly literature on this topic. (2) Methods: This study conducted a listening session with Elders who attended the 2021 National Indian Council on Aging (NICOA) Annual Conference in Reno, Nevada. The listening session was audio-recorded and transcribed for thematic analysis by two analysts. (3) Results: Important insights regarding American Indian and Alaska Native Elders’ perspectives on planning for future care and aging-related diseases, such as Alzheimer’s disease. (4) Conclusions: This study is one of the first to engage American Indian and Alaska Native Elders in a conversation about health aging. Calls for intergenerational solidarity, protection of Elders, education, and relationality were found to be important themes.